Financial, Institutional, and Macroeconomic Determinants of Cross-Country Portfolio Equity Flows - António Afonso; José Alves; Krzysztof Beck; Karen Jackson (Center for Economic Studies and ifo Institute (CESifo), 2022)
We consider a new dataset that provides a description of the population of financial equity flows between developed countries from 2001 to 2018. We follow the standard practice of controlling for pull and push factors as well as gravity-style variables, while also accounting for the business cycle, public debt and sovereign ratings. Our key findings are as follows: (i) equity flows are more intense between countries at the same stage of the business cycle (ii) increased equity flows to countries with a relatively lower public debt deficit as a ratio of GDP (iii) financial and macroeconomic variables are important for big equity flows, while institutional variables are important for the small flows. Overall, this new dataset provides novel evidence on the importance of the business cycle, government debt and sovereign ratings scores.
Keywords: C23; E44; F44; G15; 330; cross-country equity flows; stock market returns; panel data; quantile regression; business cycle